Similarity between Effects of Laves Phase and M6C in Alloy Steels - Janovec, Jozef (Communications - Scientific letters of the University of Zilina, 2009)
The aim of this work is to summarize the experimental result obtained within the last two decades about the effects of Laves phase and M6C during long-term thermal exposures of alloy steels. The intergranular Laves phase (12CrMoV steel) and/or M6C (3CrMoV steel) particles were found to evoke the anomaly in the kinetic dependence of phosphorus grain boundary concentration. In comparison to other phases usually present in Cr-Mo alloy steels, Laves phase and M6C precipitate after longer periods of annealing and dissolve non-metallic elements such as phosphorus or silicon. A partitioning of originally segregated phosphorus between the matrix and the newly precipitated Laves phase and/or M6C particles led to the decrease in the phosphorus grain boundary concentration.